Educational Leadership Concepts in Hadith Mas'ūliyyah and Gundul-Gundul Pacul ; A Weberian Perspective - Muhammad Rijal Mushthofa; Nuri Safitri; Masruhan Masruhan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study examines leadership ethics through the integration of hadith mas’uliyah, Max Weber’s theory of authority, and the philosophical values of the Javanese traditional song Gundul-Gundul Pacul. Previous studies generally discuss Islamic leadership, Weberian authority, and local wisdom separately without constructing an integrative framework among them. This research employs qualitative library research using descriptive-analytical and hermeneutic approaches. The findings reveal that both hadith mas’uliyah and Gundul-Gundul Pacul emphasize leadership as moral responsibility grounded in accountability, humility, and public service. Through Weber’s perspective, these traditions reflect traditional, charismatic, and rational-legal authority simultaneously. This study proposes the “Wakul Leadership Model” as a conceptual synthesis integrating Islamic ethics, sociological legitimacy, and Javanese local wisdom. The model contributes to the development of contextual and ethical leadership discourse in contemporary Indonesian society.